Mortalité de Crassostrea gigas dans le bassin de Marennes Oléron. Etude physico chimique du sédiment. Etude du modèle de mortalité "plat-table" de C. gigas dans le bassin de Marennes Oléron. Etude "Dynamo" du projet MOREST - Soletchnik, Patrick; Bouchet, Vincent; Malestroit, Pascale; Seugnet, Jean-luc; Blouin, Frederic; Radford-knoery, Joël; Burgeot, Thierry; Sauriau, Pierre-guy (2005)
In the scope of the study of the "on-bottom/off-bottom" mortality model in the south of the Marennes Oléron Bay, the result of the 2003 multidisciplinary study (Dynamor) appears to be the hypothesis of an acute stress, "ultimate" trigger of the mortality episodes in June. In 2004 we aim to look for the nature of this stress through the physico-chemical analysis of the sediment (Eh, pH, sulphides and ammoniacal nitrogen), the organic matter and chlorophyll load on the surface of the sediment between April and July. Herbicides are also measured in the water column, south of the bay (Seudre), during the same period. A "precocious" (around the first week of June) and "weak" (lower mortality rate on this working site since 1997) mortality peak happens when the average sea water temperature is still lower than 18°C. The hypothesis is the following: following the degradation of the organic matter, the ammoniacal nitrogen flux develops a few centimetres inside the sediment. This degradation intensifies in May-June when successive anticyclonic episodes warm up the sediment. At around 19°C, the bacterial degradation of the organic matter accelerates, releasing an important ammoniacal nitrogen flux that the microphytobenthos cannot totally consume. Under the probable action of the NH3 ion, the phytoplankton dies (drop of the chlorophyll level from 300 to 80 mg m-2) causing a mini dystrophic crisis (or mini "malalaïgue"!). The nitrite peak will be identified later in June. This organic matter degradation process under bacterial action is strongly linked with thermic conditions, and could explain the correlation between the temperature of 19°C and some mortality episodes. The analogy of the thermic profiles obtained 15cm inside the sediment and during slack water at high tide explains (1) the direction of the study decided upon in looking for the causes of mortality in the water column and (2) its re-direction towards the sediment. The foraminifer Ammonia tepida seems to be an excellent marker throughout this sensitive ...